Dual roles of [NCN]2- on anatase TiO2: A fully occupied molecular gap state for direct charge injection into the conduction band and an interfacial mediator for the covalent formation of heterostructured g-C3N4/a-TiO2 nanocomposite - Nimbalkar, Dipak B.; Ramacharyulu, P.V.R.K.; Sahoo, Smruti R.; Chen, Jun-Ru; Chang, Chun-Ming; Maity, Amarendra N.; Ke, Shyue-Chu (Applied catalysis. B, Environmental, 2020)
[Display omitted] •The strategy of low melamine/TiO2 ratio isolates a NCN2−—TiO2 transient species.•NCN2−—TiO2 exhibits excellent activities in H2 production, a novel photocatalyst.•Admixture of NCN2− HOMO π2p with Ti 3d upshifts the state into the bandgap of TiO2.•Five-line EPR pattern from a hole at NCN1−—TiO2, authentication of a gap state.•Heterostructured g-C3N4/TiO2 formation proceeds via the intermediacy of NCN2−—TiO2. When low density of melamine is calcined with a-TiO2 at 550 °C, two FT-IR peaks observed at 2048 and 2066 cm−1 are assigned to NCN2- covalently attached to a five-coordinated Ti atom and an oxygen vacancy, respectively, complemented by DFT computation. Admixture of NCN2- HOMO(π2p, 87.5 %) with the high energy Ti(3d, 12.5 %) destabilizes and upshifts the NCN2- HOMO into the a-TiO2 bandgap. A five-line EPR pattern derived from 71 % of atomic spin density localized on two equivalent 14N nuclei, observed under sub-bandgap excitation, verifies the presence of a molecular gap-state. The NCN2--a-TiO2 exhibits excellent H2 production at a rate of 5101 μmol.h-1.g-1. Upon increasing melamine concentration, the rapid and simultaneous decreases of NCN2- FT-IR and NCN1- EPR signals accompanied by transitions of other spectroscopic data to those characteristic of tri-s-triazine demonstrate that the formation of heterostructured g-C3N4/a-TiO2 proceeds via the intermediacy of NCN2--a-TiO2, thereby a mechanism is proposed.